2020
DOI: 10.1101/2020.08.13.20171751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification on Admission of COVID-19 Patients at Risk of Subsequent Rapid Clinical Deterioration

Abstract: Introduction: Recent localized surges in COVID-19 cases have resulted in the hospitals serving those areas being overwhelmed. In such cases, the ability to rapidly and objectively determine a patient's acuity and predict near-term care needs is a major challenge. At issue is the clinician's ability to correctly identify patients at risk for subsequent rapid clinical deterioration. Data-driven tools that can support such determinations in real-time may be a valuable adjunct to clinician judgement during COVID-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…A recent study conducted by PeraHealth, the developers of RI, has shown that RI has some use in risk stratification for patients with COVID-19; however, the accuracy and effectiveness of its implementation are of unknown significance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study conducted by PeraHealth, the developers of RI, has shown that RI has some use in risk stratification for patients with COVID-19; however, the accuracy and effectiveness of its implementation are of unknown significance [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Candidate predictors (i.e., laboratory, demographic, and clinical parameters) were selected from existing models and published literature 6,7,9,11,12,20,21 and included age, sex, Acute Physiology and Chronic Health Evaluation II (APACHE II) score at the time of ICU admission, 22 respiratory rate, oxygen requirements and saturation, temperature at admission, white blood cell count and lymphopenia, end-organ dysfunction (including acute kidney injury and evidence of hepatic injury through elevations of hepatic enzymes), and preadmission patient comorbidities (e.g., hypertension, diabetes, coronary artery disease, current smoker, pulmonary disease). Data on biomarkers such as albumin, procalcitonin, ferritin, d-dimer, C-reactive protein (CRP), lactate dehydrogenase, and erythrocyte sedimentation rate were collected where available.…”
Section: Selection Of Potential Predictive Variablesmentioning
confidence: 99%